Pendidikan Inklusif Bagi Anak Berkebutuhan Khusus - Hibana, Hibana (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga Yogyakarta, 2019)
The purpose of this study is to understand how the concept of inclusive education for earlychildhood and how the application in ECE (Early Childhood Education) institutions in serving children with special needs (Exceptional Children) following current community needs. The study was done through library research. This method consisted of several steps, namely collecting data and information from various books and materials in the library. Reading sources used such as reference books, scientific journals, newspapers, magazines and electronic media. Therefore, the study can be concluded as follows. Three main things related to the implementation of inclusive services, namely 1). Understanding the characteristics of children and their special needs, 2) Building a comfort nuance when interacting with children, and 3) Building a child's closeness. It is necessary to make an inclusion class in purpose to realize the inclusive service. Related to Inclusion Class, there are some conclusions related to that topic, namely. 1)Managing learning environments that accommodate children with special needs. 2) applying peer tutoring. 3) carrying out scaffolding strategies, 4) Developing social acceptance of children with special needs (Exceptional Children) 5) Guiding and directing the behavior of all students. Indeed, they can accept and behave positively toward children with special needs (Exceptional children)